An Unusual Case of Gallium Scan Mimicking a Bone Scan - Puranik,Ameya; Luthra,Karuna; Lele,R. D.
Gallium-67 localization is based on the fact that it binds to plasma proteins like transferrin and lactoferrin, which have iron-binding sites. Abnormal biodistribution of gallium-67 citrate can occur in iron-overload states. We report one such case of gallium scan mimicking a bone scan due to skeletal uptake of gallium.